Scientific research on introduced wildlife in New Zealand: For whom and at what cost? - Steer, Jamie (New Zealand Science Review, 2015)
In his keynote address to the 2015 New Zealand Association of Scientists Annual Conference, Professor Peter Gluckman offered a timely reminder to New Zealand scientists: that their legitimacy within public discourse and decision making is ultimately founded in integrity and trust (Gluckman 2015). Reflecting on the growth of new information and media sources in the last few decades, and the erosion in trust in the more established ones, Professor Gluckman urged scientists to adhere to the features that distinguish science from other epistemologies. He also asked New Zealand scientists to consistently recognise and acknowledge the limits of scientific knowledge and the unhelpful biases that can creep into its production (also see Gaston 2015). With these thoughts firmly in mind, this article traces a short history of natural science research on introduced wildlife in New Zealand. Through this history, I argue that a maintenance of public trust in New Zealand natural scientists will require (1) more consistent self-reflection to identify and communi-cate the assumptions and predispositions of their research and (2) more active endorsement and support for research that investigates the questions that are not considered useful to ask. I argue that if these points are not considered and adequately addressed, New Zealand’s natural scientists risk substantiating the claim that their science is compromised by undisclosed value frameworks or that their analyses are simply another tool being used to further the agendas of their employers. To narrow what might otherwise prove a formidably broad topic, I focus my history on a subset of introduced game species – specifically mallard ducks (Anas platyrhynchos), deer and trout (various species). I employed a critical discourse approach (Phillips & Hardy 2002) to interviewing and documentary research, grounding this approach in a broad social constructionist perspective (Burr 2003). For a full explanation of my methodology and information sources refer to Steer (2015). I do not intend this analysis to be comprehensive. It is offered merely as a contribution to the discussion of how the New Zealand natural science community, in particular, might choose to refine their practice and thereby maintain a credible seat at the decision-making table.